2021
DOI: 10.1002/aet2.10702
|View full text |Cite
|
Sign up to set email alerts
|

Rapid‐cycle deliberate practice improves time to defibrillation and reduces workload: A randomized controlled trial of simulation‐based education

Abstract: Background The optimal structure of simulation to train teams to perform pediatric advanced life support (PALS) requires further research. Most simulation is structured with an uninterrupted scenario with postsimulation debriefing (PSD). Rapid‐cycle deliberate practice (RCDP) is structured with a series of simulations with microdebriefing quickly switching within action targeting specific performance goals. Objective The objective was to compare team performance immediately after training, as well as learner w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 49 publications
(57 reference statements)
0
19
0
4
Order By: Relevance
“…Although studies have shown good performance in resuscitation efforts of teams after RCDP was applied [7][8][9], as well as in simulated scenarios of intra-hospital CPR compared to the standard course of basic life support (BLS) [10,11], so far there have been no studies comparing the after-event debriefing method of clinical simulation versus rapid-cycle deliberate practice for advanced CPR training in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies have shown good performance in resuscitation efforts of teams after RCDP was applied [7][8][9], as well as in simulated scenarios of intra-hospital CPR compared to the standard course of basic life support (BLS) [10,11], so far there have been no studies comparing the after-event debriefing method of clinical simulation versus rapid-cycle deliberate practice for advanced CPR training in adults.…”
Section: Introductionmentioning
confidence: 99%
“…O número total de artigos foi 790, após exclusão de duplicados 492 foram analisados pelos títulos e resumos. 22 foram selecionados para leitura completa do artigo e desses 12 compõem a revisão 1,[8][9][10][11][12][13][14][15][16][17][18] (Figura 2).…”
Section: Resultsunclassified
“…Treinamento prévio do instrutor para ensino por técnicas de PDCR e simulação tradicional, participação em curso de instrutor, workshops, coreografias pré definidas e constante avaliação/ monitorização dos instrutores pelos pares e por experts são alguns exemplos mencionados. [8][9][10][11] Os temas envolvidos no uso de PDCR para reanimação cardiopulmonar pediátrica variaram entre aquisição de habilidades técnicas críticas para reanimação de alta qualidade, trabalho em equipe, melhoria de desempenho, retenção destas habilidades ao longo do tempo assim como percepção e satisfação dos participantes com esta técnica.…”
Section: Resultsunclassified
See 2 more Smart Citations